Erratum: A little inflation in the early universe at the QCD phase transition [Phys. Rev. Lett. 105, 041301 (2010)] - Boeckel, Moritz Tillmann; Schaffner-Bielich, Jürgen (Physical review letters, 2011)
DOI:https://doi.org/10.1103/PhysRevLett.106.069901
Gesehen am 01.02.2023